Graphene quantum dots induce cascadic apoptosis via interaction with proteins associated with anti-oxidation after endocytosis by Trypanosoma brucei - Xie, Yiwei; Liang, Hongrui; Jiang, Ning; Liu, Dingyuan; Zhang, Naiwen; Li, Qilong; Zhang, Kai; Sang, Xiaoyu; Feng, Ying; Chen, Ran; Zhang, Yiwei; Chen, Qijun (Frontiers in Immunology, 2022)
Trypanosoma brucei, the pathogen causing African sleeping sickness of humans, causes debilitating diseases in many regions of the world, mainly in African countries with tropical and subtropical climates. Enormous efforts have been devoted to controlling trypanosomiasis, including expanding vector control programs, searching for novel anti-trypanosomials agents, and vaccine development, but with limited success. In this study, we systematically investigated the effect of graphene quantum dots (GQDs) on trypanosomal parasites and their underlying mechanisms. Ultrasmall-sized GQDs can be efficiently endocytosed by T. brucei and with no toxic to mammalian-derived cells, triggering a cascade of apoptotic reactions, including mitochondrial disorder, intracellular reactive oxygen species (ROS) elevation, Ca2+ accumulations, DNA fragmentation, adenosine triphosphate (ATP) synthesis impairment and cell cycle arrest. All of these were caused by the direct interaction between GQDs and proteins associated with cell apoptosis and anti-oxidation responses, including trypanothione reductase, a key protein in anti-oxidation. GQDs specifically inhibit the enzymatic activity of trypanothione reductase, leading to reduction in antioxidant capacity and ultimately parasite apoptotic death. The data, for the first time, provide a basis for the exploration of GQDs in the development of anti-trypanosomials.